Meta‐analysis of bivalirudin versus heparin in transradial coronary interventions. Issue 6 (24th February 2020) - Kheiri, Babikir; Rao, Sunil V.; Osman, Mohammed; Simpson, Timothy F.; Barbarawi, Mahmoud; Zayed, Yazan; Dhillon, Harsukh N.; Alkhouli, Mohamad; Golwala, Harsh; Zahr, Firas; Bhatt, Deepak L.; Stone, Gregg W.; et al.
Abstract: Objectives: We sought to evaluate the efficacy and safety of bivalirudin versus heparin in patients with coronary artery disease undergoing transradial artery coronary intervention (TRI). Background: Bivalirudin and radial artery access are independently associated with improved cardiovascular outcomes. However, data supporting a strategy of combining both to achieve additive improvements in cardiovascular outcomes provide conflicting results. Methods: A systematic search was performed to identify randomized controlled trials (RCTs) of bivalirudin, in which vascular access sites were reported. The primary outcome was net adverse clinical events (NACE) at 30 days. Secondary outcomes were long‐term NACE, short‐, and long‐term major adverse cardiovascular events, all‐cause mortality, myocardial infarction, unplanned revascularization, stent thrombosis, and major bleeding. Results: We identified 10 RCTs, including 16, 328 patients who underwent TRI (mean age 64.6 ± 15.7 years, 72.5% male). Bivalirudin use was associated with decreased 30‐day NACE compared with heparin (6.3 vs. 7.4%; risk ratio [RR] = 0.87; 95% confidence interval [CI] = 0.76–0.99; p = .04; number needed to treat = 91). No significant interactions were observed based on clinical presentation, administration of P2Y12 inhibitors, or glycoprotein IIb/IIIa‐receptor inhibitors (GPI) use. There were no significant differences between groups in any prespecified secondary outcomes. There was, however, a significant reduction of major bleeding in the bivalirudin group compared with heparin when used in combination with routine GPI (RR = 0.41; 95% CI = 0.19–0.90; p = .03). Conclusions: Among patients undergoing TRI, use of bivalirudin was associated with significantly reduced 30‐day NACE compared with heparin. There was no significant difference in long term NACE, ischemic, or bleeding events compared with heparin.